Factores de la dimensión afectiva asociados a las reacciones frente evaluaciones en matemática: la experiencia de dos jóvenes estudiantes destacados académicamente - Vargas-Díaz, Claudia; Matus Correa, Claudia (Innovaciones Educativas, 2022)
In this article, we identify a Chilean educational establishment in the Metropolitan Region of Santiago, where gender gaps were reverted in mathematics tests results. By exploring the affective factor on school performance and applying and analyzing the concomitance between the answers given in a survey that measures emotions and anxiety towards mathematics. The survey was applied to two academically gifted students (one male and one female) to determine the differences in their emotions regarding mathematicsrelated school activities. Subsequently, we interviewed the male student. Differences were identified in affective factors, as well as in this student’s experience during the mathematics evaluations in his school days, through analyzing his speech and using creative interpretation. The results concluded that different affective states are provoked among the participants facing the same school activities related to mathematics. Said differences were not associated with the level of self-efficacy, assessment or performance in mathematics expressed by the participants. In addition, insecurity not related to the content domain was detected when examining, in detail, the speech of the male participant.